The Development of Statistics Modules for the Students of Islamic Colleges and Universities in South Tapanuli - Ahmad Nizar Rangkuti; Latifa Annum Dalimunthe; Ali Asrun Lubis (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
This study aims to develop a statistical module for the students of Islamic colleges and universities in South Tapanuli. Research and Development (RD) with Instructional Development Institute (IDI) model was implemented. This research consists of three stages, namely, the front-end analysis stage, the prototype stage, and the assessment stage. The results of the study showed that the statistical module that was designed was valid including content validity and construct. The result also showed the use of statistical modules in the learning process does not experience significant obstacles, in the practical sense of their use according to the assessments of observers and students and lecturers. It indicated that the statistical module has been effective which is shown from the results of observations on the implementation of the learning process, the results of interviews with lecturers and students, as well as higher student learning outcomes using modules in learning.